Surface patterning of wide-gap semiconducting β-Ga2O3 thin films by area selective crystallization via room-temperature excimer laser annealing and low-toxic wet etching processes - Daishi Shiojiri; Ryoya Kai; Satoru Kaneko; Akifumi Matsuda; Mamoru Yoshimoto (Applied Physics Express)
In the present study, we have developed a fully room-temperature and low-toxic surface patterning method for β -Ga _2 O _3 , which consists of the area selective laser-induced crystallization of amorphous Ga _2 O _3 thin films and acid solution etching processes. Highly ( $\bar{2}$ 01)-oriented crystalline β -Ga _2 O _3 thin films with ∼70 nm thickness on α -Al _2 O _3 (0001) substrates were obtained through a combination of room-temperature deposition process and the subsequent excimer laser annealing at a deep ultraviolet wavelength of 248 nm. In conclusion, the area selective crystallized β -Ga _2 O _3 micropatterns were obtained through ultrasonic wet etching with 40% H _3 PO _4 aqueous solution to remove amorphous regions.